Performance management by co-operating and participating. Lessons learned from transfering service responsibiliy from state to municipal level - Ólafsson, Óskar Dýrmundur (Stjórnsýslustofnun, 2011)
Learning from decentralization of services from state to municipal level: The transfer of services from state to municipality level in the past 15 years has created an environment for learning and provides opportunities for development and innovation. This article is mainly based on findings from a case study in Akureyri, a municipality in north Iceland, which did implement services from the state to the municipal level and has been called the Akureyri model. The change was made possible by a legislative change in 1994. The case study is based on qualitative interviews with management personel about their management methods during implementation and data collection from previous sources. Findings show that cross-professional methods, wholistic solutions and a service orientated approach matter for performance. The organizational structure of the municipality support these methods and can improve performance. When managing municipalities it is recommended to put more emphasize on empowerment, learning and enable possibilities to increase efficiency by systems thinking. Yfrfærsla á þjónustu frá ríki til sveitarfélaga sem hefur átt sér stað síðastliðinn 15 ár hefur stuðlað að þróun og nýsköpun hjá sveitarfélögunum. Því er gagnlegt að líta til reynslu þeirra og draga fram lærdóm um slíkar breytingar. Þessi grein byggir meðal annars á niðurstöðum tilviksrannsóknar um stjórnun Akureyrarbæjar við yfirfærslu þjónustu frá ríki til sveitarfélaga. Hófust breytingarnar með lögum frá 1994 og gengu undir heitinu Akureyrarlíkanið. Tekin voru sex viðtöl við stjórnendur bæjarins og reynsla þeirra af yfirfærslunni sem og aðferðir við stjórnun skoðuð. Fram kom að árangur þeirra byggðist meðal annars á þverfaglegu samstarfi, heildstæðum lausnum og þjónustu sem byggist fyrst og fremst á þörfum íbúa. Skipulag sveitarfélaga hentaði vel til þess að ná þessum árangri. Fram kemur að við stjórnun þeirra er heppilegt að líta í ríkari mæli til valdeflingar, lærdóms og möguleika til aukinnar skilvirkni með kerfishugsun.